CONSTITUTIONAL AND PENAL LAW ASPECTS OF THE PROTECTION OF FREEDOM OF CONSCIENCE AND CONFESSION (RELIGION) IN POLAND - Zbigniew, Witkowski; Piotr, Chrzczonowicz; Witkowska, Chrzczonowicz Katarzyna (Anales Universitatis Apulensis Series Jurisprudentia, 2012)
The authors outline the constitutional and penal law issue of protection of freedom of conscience and confession (religion) in Poland. In this context, not only do they indicate the relevant legal regulations, but also the views of doctrine, and at some noteworthy practical problems, which generated public debate and media interest in the last decade. The authors express the assumption that the current state of democracy in Poland, the issue of realization of freedom of conscience and confession (religion), which remains a controversial issue, will stimulate further social discourse. It seems that the current constitutional regulations in Poland and penal law solutions are sufficient to ensure respect for human rights to freedom of conscience and confession (religion). The biggest challenge remains the practice of application of these regulations, as probably the tendencies shown above will bring about more and more cases of mentioned freedom to the Constitutional Tribunal, as well as more and more reports of such crimes being committed, such as offending religious feelings. Most probably the judicature will show the directions of Polish changes in this regard. Keywords: constitutional law, penal law, protection of freedom of conscience and confession, state of democracy, social discourse, human rights, Constitutional Tribunal